Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1995
DOI: 10.1115/95-gt-005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adverse Pressure Gradients on Momentum and Thermal Structures in Transitional Boundary Layers: Part 2 — Fluctuation Quantities

Abstract: The effects of adverse pressure gradients on the thermal and momentum characteristics of a heated transitional boundary layer were investigated with free-stream turbulence ranging from 0.3 to 0.6%. Boundary layer measurements were conducted for two constant K cases, K1=-0.51 x 10-6 and K2=-1.05 x 10-6 .The fluctuation quantities, u', v', t', the Reynolds shear stress Downloaded from https://asmedigitalcollection.asme.org/GT/proceedings-pdf/GT1995/78811/V004T09A005/2406406/v004t09a005-95-gt-005.pdf by guest on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The computed u profile at this location shows a good qualitative match with its experimental counterpart and, in particular, exhibits a plateau in the region 10 y 30, albeit less marked than in the experiment. Mislevy and Wang [43] showed that this plateau in the early stages of transition is due to the presence of an adverse pressure gradient by comparing fluctuation profiles in transitioning boundary layers subject to different adverse pressure gradients. The height at which the maximum fluctuation levels are reached is slightly lower in the computational results, at approximately y ' 30, to be compared with the value of y ' 40 obtained experimentally.…”
Section: A Mean Flowfieldmentioning
confidence: 99%
“…The computed u profile at this location shows a good qualitative match with its experimental counterpart and, in particular, exhibits a plateau in the region 10 y 30, albeit less marked than in the experiment. Mislevy and Wang [43] showed that this plateau in the early stages of transition is due to the presence of an adverse pressure gradient by comparing fluctuation profiles in transitioning boundary layers subject to different adverse pressure gradients. The height at which the maximum fluctuation levels are reached is slightly lower in the computational results, at approximately y ' 30, to be compared with the value of y ' 40 obtained experimentally.…”
Section: A Mean Flowfieldmentioning
confidence: 99%